Management of Linguatula serrata infestation in a dog from Greece: a case report - Lefkaditis, M; Zapantes, I; Giannouli, A (Journal of the Hellenic Veterinary Medical Society, 2023)
Linguatuliasis is caused by the Arthropod parasite Linguatula serrata (family: Linguatulidae) a parasite with worldwide distribution and zoonotic importance, especially in warm subtropical and temperate regions. Dogs, cats, foxes, jackals, and other carnivores are the final hosts of this Arthropod while any mammal could be a potential intermediate host of this parasite. Adults L. serrata live in the nasopharyngeal region and lower respiratory system, embed their body into the mucosa of nasal pharyngeal cavities. A two year old spayed female dog of undetermined breed, weighting 29 kg that lives in a mountain village called Sella (Prefecture of Achaia, Greece) in a semi-free form, was presented in a veterinary clinic of Patra with history of progressive cough and sneezing, which started about 2 weeks earlier. Along with the dog, the owner brought a parasite that was expelled from the dog’s nose during the intense cough and sneezing the same day. Macroscopic morphological aspects of the parasite, in the laboratory under stereoscope, revealed an arthropod 3,8cm in length identified as L. serrata, also commonly called tongue worm. The dog was treated with Macrocyclice lactone and lavage of nasal cavities. Humans can become infected in two ways: either as an intermediate host (visceral linguatuliasis) or as an accidental final host (nasopharyngeal linguatuliasis), usually as a result of consumption of raw or poorly cooked meat of an infected intermediate host.